PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA ORGANISASIONAL TERHADAP STRES KERJA PEGAWAI: KAJIAN DI KANTOR KOMISI PEMILIHAN UMUM KABUPATEN/KOTA SE PULAU LOMBOK - Sansuri Sansuri (Master of Management, Mataram University, 2015)
The objecives of this study were (1) to determine whether the workload significantly effectsthe employee depression, (2) to determine wether the comfort of working may weaken the effect ofqualitative excessive burden on employee depression, (3) to determine whether familiarity with coworkerwill weaken the effect of qualitatively excessive burden on employee depression, (4) todetermine whether the availability of working facility may weaken the effect of quantitativeexcessive burden on depression of employees of KPU in all districts on Lombok. This research isassociative research. Respondens are 45 people taken by the census. The instrument of datacollection in this study is questionnaire. The statistical analysis used was analysis ModeratedRegression Analysis (MRA) using SPSS for Windows version 16.0.The research showed (1) either quantitative or qualitative workload of the members of theorganization in general can make employee depressed, (2) qualitatively excessive burden whensituated in comfortable working situation does not effect employee depression, (3) qualitativelyexcessive burden negatively effects the employee depression when situated in familiarity with coworkersthat would weaken the effect of the depression of the employee, (4) qualitatively excessiveburden positively effects the depression of the employye if situated in the availability of adequateworking facilities. Depression may occur if the updates/rejuvenation of working facilities areoptimally done and this may strengthen the effect of the depression of employee in all districts on theisland of Lombok.Keywords : Workload, Working Environment, Work Depression